2010
DOI: 10.1203/pdr.0b013e3181ef7619
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Mask Airway for Surfactant Administration in a Newborn Animal Model

Abstract: Premature infants are subjected to adverse effects of intubation to benefit from surfactant. We hypothesized that administration of surfactant through a laryngeal mask airway (LMA) is as effective as administration through an endotracheal tube (ETT) and that time and physiologic changes during instrumentation will be less in the LMA group. This study is a randomized, controlled trial using newborn pigs. Lung injury was induced via surfactant washout. Animals were randomized into groups: 1) LMA placed, no surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Reports on surfactant application via laryngeal mask are interesting but refer to only a small number of patients. 22,23 Administration of surfactant via a thin catheter during spontaneous breathing with CPAP has been used since 2001. In this method, generally the catheter is placed with Magill forceps into the trachea under direct laryngoscopy and surfactant is applied over a period of 1 to 3 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…Reports on surfactant application via laryngeal mask are interesting but refer to only a small number of patients. 22,23 Administration of surfactant via a thin catheter during spontaneous breathing with CPAP has been used since 2001. In this method, generally the catheter is placed with Magill forceps into the trachea under direct laryngoscopy and surfactant is applied over a period of 1 to 3 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…This is also the case in adult (Goldmann and others 2005) and neonatal (Roberts and others 2010) pigs. In rabbits, known to present narrow mouth opening and poor visualisation of the larynx inlet, LM could be placed in 8 to 12-fold less time than endotracheal intubation was achieved, especially for anaesthetists with little experience (Smith and others 2004).…”
Section: Discussionmentioning
confidence: 67%
“…The use of a laryngeal mask (LM) is an appropriate alternative to endotracheal intubation, providing an airtight seal around the laryngeal inlet with the option to ventilate the animal if necessary (Wemyss-Holden and others 1999, Fulkerson and Gustafson 2007). Its use in neonate swine has been described once by Roberts and others (2010) as safe, uncomplicated and rapid. Moreover, the LM has been used to achieve ventilation in human patients in whom tracheal intubation or ventilation through facemask has failed (Asai 1996); it thus has a potential role in patients with difficult airways.…”
Section: Introductionmentioning
confidence: 99%
“…In an animal study comparing ETT to LMA surfactant delivery, it was reported that surfactant delivery could be accomplished sooner in the LMA group with equivalent efficacy. 85 7 In animal studies, distribution of intratracheally instilled surfactant has been largely determined by gravity, and unaffected by the position of the chest. 89 Therefore, leaving the chest in a horizontal position may result in the most even distribution of surfactant to the lungs.…”
Section: Laryngeal Mask Airway (Lma) Administrationmentioning
confidence: 99%